In order to do this problem, you need to multiply directly. So, 2 over 3 times 6 over 7. First, we're going to do the top. 2 times 6 is 12. The bottom is 3 times 7, which is 21. Your answer is 12 over 21, but they can be both reduced by 3, so your final answer is 4 over 7.
Chat with our AI personalities
2/3 = (2 x 2)/(3 x 2) = 4/6 4/6 is greater than 1/6, so yes.
Set up the equation and solve for x: 2/3(x) - 6 = -10 (next add 6 to each side to separate knowns from unknowns) 2/3(x) = -4 (next multiply both sides by 3 to simplify) 2x = -12 (next divide both sides by 2 to solve for x) x = -6 to prove: substitute x with -6 (hint: 2/3 of -6 = -4) 2/3(-6) - 6 = -10 -4 - 6 = -10 -10 = -10
We can simply write 3 fifths=3/5 ,2 thirds=2/3 & 1 half=1/2 . So, we can write it in mathematicaly as below, =3/5 x 2/3 x 1/2 in upper term 3 & 2 are comman in numerator& denometer.so, they will disappear from the term . After that term will be like below. =1/5 or =0.2 which is the answer
Y = - X^2 + X + 6 set to 0 - X^2 + X + 6 I always multiply through by - 1. Different direction graph, but same 0's -1(-X^2 + X + 6 = 0) X^2 - X - 6 = 0 what two factors of - 6 add up to - 1 ? (X - 3)(X + 2) ----------------------Now, X = 3 X = -2 As functions zeros
2/3 x 2400 = 4800/3 = 1600